Economical management of loose smut of wheat with propiconazole - RANA, S K; BASANDRAI, A K; SOOD, A K; SHARMA, B K (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1994-95 and 1995-96 to work out a cheaper seed treatment for the control of loose smut of wheat with triazole fungicides, viz tebuconazole (Raxil), difenoconzole (Score and Dividend) and propiconazole (Tilt). Of these the wet treatment with Tilt by dipping the seed in 0.01% solution for 6 hr and dry seed treatment with Raxil (0.1%) werc most effective. The former proved duite economic, costing just Rs 15.00/100 kg of seed as compared to Rs 188.00 with carboxin (Vitavax)